CORRELATION BETWEEN INTERPERSONAL COMMUNICATION AND LEADERSHIP COMMUNICATION WITH THE EMPLOYEE PERFORMANCE OF THE DPD RI SECRETARIAT-GENERAL - Sila Nirmala (Universitas prof. Dr. Moestopo (Beragama), 2021)
This research was carried out by formulating the following problems: (1) Is there a relationship of leadership communication with the performance of the DPD Secretariat General's staff? (2) Is there a relationship between interpersonal communication and the performance of the DPD Secretariat General's staff? (3) Is there a relationship between leadership communication and interpersonal communication with the performance of employees of the DPD Secretariat General? To answer the formulation of the problem above, this research was conducted with a survey method with a quantitative approach, namely associative descriptive. The population in this study were employees of the DPD Secretariat General, with a sample of 90 people. Sampling method using a purposive sampling method. The data collection method used is the questionnaire method. The data analysis method used is the analysis of partial correlation and multiple correlation analysis. The results showed that: (1) The relationship between leadership communication and employee performance obtained the number t-count (3.091)> t table (2,675), a significant number of 0,000 <0,05 and, a correlation number of 0,500 (25%) means that there is a significant relationship. (2) The relationship between interpersonal communication and employee performance is obtained by the number t-count (7.105)> t-table (2.675), a significant number of 0.000 <0.05 and, a correlation number of 0.711 (50.5%) means that there is a significant relationship. (3) The relationship between leadership communication and interpersonal communication with employee performance obtained Fcount number (11,626)> F-table (1,605) significant number 0,000 <0,05 and correlation number 0,795 (63,2%) means that there is a significant relationship.